Global, regional, and national burdens of type 1 and type 2 diabetes mellitus in adolescents from 1990 to 2021, with forecasts to 2030: a systematic analysis of the global burden of disease study 2021 - Xing Chen; Luying Zhang; Wen Chen (BMC Medicine)
Abstract Background Adolescent diabetes is one of the major public health problems worldwide. This study aims to estimate the burden of type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) in adolescents from 1990 to 2021, and to predict diabetes prevalence through 2030. Methods We extracted epidemiologic data from the Global Burden of Disease (GBD) on T1DM and T2DM among adolescents aged 10–24 years in 204 countries and territories worldwide. This study calculated the age-standardized prevalence rate (ASPR) and age-standardized DALY rate (ASDR) in adolescents based on the world standard population for cross-country comparisons. Average annual percentage changes (AAPC) in age-standardized rate were calculated by linkage point regression. Correlation analyses were used to identify the relationship between age-standardized rate and sociodemographic index (SDI). The Bayesian age-period-cohort (BAPC) model was used to predict changes in the diabetes prevalence among adolescents from 2022 to 2030. Results In 2021, 3.4 million adolescents were living with T1DM, with an ASPR of 180.96 (95% CI 180.77–181.15), and 14.6 million were living with T2DM, with ASPR of 1190.73 (1190.13–1191.34). As national and territory SDI levels rise, the prevalence rate of T1DM increases (r = 0.44, p < 0.01), and the prevalence rate of T2DM decreases (r = − 0.18, p < 0.01). Compared with males, females had a greater age-standardized prevalence of T1DM (185.49 [185.21–185.76] vs. 176.66 [176.39–176.92]), whereas males had a greater ASPR of T2DM than females did (1241.45 [1240.58–1242.31] vs. 1138.24 [1137.40–1139.09]). This study found a negative correlation between the SDI and the ASDR for both T1DM (r = − 0.51, p < 0.01) and T2DM (r = − 0.62, p < 0.01) in adolescents. For T2DM patients, 32.84% of DALYs were attributed to high BMI, which increased by 40.78% during the study period. By 2030, 3.7 million people are projected to have T1DM, and 14.6 million are projected to have T2DM. Conclusions Among adolescents, the burden of T1DM and T2DM is increasing and varies by region, sex, and SDI. Therefore, targeted interventions based on regional features are needed to prevent and control adolescent diabetes. Moreover, more efforts are needed to control climate change and obesity to reduce the adolescent diabetes burden.